2013
DOI: 10.1177/1474474012469761
|View full text |Cite
|
Sign up to set email alerts
|

Opening Ungava to industry: a decentring approach to indigenous history in subarctic Québec, 1937–54

Abstract: This article examines the period leading up to the establishment of the Schefferville iron mine in subarctic Québec, Canada, with a focus on the years 1937–54. The beginning of iron ore mining at Schefferville was a decisive moment in the growth of the modern Québec state, opening the way for the industrial exploitation of the province’s natural resources – mineral and otherwise – in the hinterland. Relying on oral and written sources, the research emphasizes the roles and actions of Innu individuals during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…According to Smallwood, the province was set "for an era of very real development" (Smallwood n.d.). Mining employment was important to Quebec politicians too, but plans to develop iron mines also reflected a nationalist political discourse, even though the mines themselves were largely owned by private American interests, that tied northern resource development to Quebec's political-economic independence, (Bradbury, 1985;Boutet, 2014;Desbiens, 2013Desbiens, 2013.…”
Section: Canadian Mining Incentivesmentioning
confidence: 98%
See 1 more Smart Citation
“…According to Smallwood, the province was set "for an era of very real development" (Smallwood n.d.). Mining employment was important to Quebec politicians too, but plans to develop iron mines also reflected a nationalist political discourse, even though the mines themselves were largely owned by private American interests, that tied northern resource development to Quebec's political-economic independence, (Bradbury, 1985;Boutet, 2014;Desbiens, 2013Desbiens, 2013.…”
Section: Canadian Mining Incentivesmentioning
confidence: 98%
“…A few years later this concession was acquired by the Labrador Mining and Exploration Company. Both concessions were eventually acquired by Ontario mining magnate Jules Timmins who then formed a partnership with Cleveland's M. A Hanna Mining and others in order to raise the capital needed develop the region's rich iron ore resources (Boutet, 2014;Neal, 2000;Summers, 1994Neal, 2000Summers, 1994).…”
Section: Canadian Mining Incentivesmentioning
confidence: 98%
“…It is still, in other words, marked by the present absence of settler colonial and indigenous theorization. In order to avoid reifying dominant (white settler) frameworks, both political geography and settler colonial studies can engage with indigenous frameworks, particularly in ways that acknowledge their heterogeneity (Boutet, ). A growing body of work in indigenous studies challenges settler colonial meanings of land (Simpson, , ), sovereignty and jurisdiction (Bruyneel, ; Pasternak, , ), and citizenship and personhood (Gombay, ; Radcliffe, ).…”
Section: Territory/sovereigntymentioning
confidence: 99%
“…In Canada, Latin America, and Australia, indigenous attitudes toward "development" and extractive industries are complicated and are not always sites of resistance against extractive industries (Valdivia 2005;Perreault and Valdivia 2010;Stanley 2016). Boutet (2014) found that Innu in Northern Canada adapted to resource development in their territory in ways that facilitated "traditional" land use practices into participation in wage-labor work. In Chile, Camacho (2016) differentiated indigenous attitudes toward mining, development, territory, and-ultimately-water change along generational lines to demonstrate difference in indigenous attitudes toward natural resource use.…”
Section: The Moral Economy Of Navajo Coal Workersmentioning
confidence: 99%